Role of the Rapid Response System in End-of-Life Care Decisions. (November 2020) - Kim, Jung Soo; Lee, Man Jong; Park, Mi Hwa; Park, Jae Yoen; Kim, Ah Jin
Purpose: An important role of the rapid response system (RRS) is to provide opportunities for end-of-life care (EOLC) decisions to be appropriately operationalized. We investigated whether EOLC decisions were made after the RRS-recommended EOLC decision to the primary physician. Materials and Methods: We studied whether patients made EOLC decisions consistent with the rapid response team's (RRT) recommendations, between January 1, 2017, and February 28, 2019. The primary outcome was the EOLC decision after the RRT's recommendation to the primary physician. The secondary outcome was the mechanism of EOLC decision-making: through institutional do-not-resuscitate forms or the Korean legal forms of Life-Sustaining Treatment Plan (LSTP). Results: Korean LSTPs were used in 26 of the 58 patients who selected EOLC, from among the 75 patients for whom the RRS made an EOLC recommendation. Approximately 7.2% of EOLC decisions for inpatients were related to the RRT's interventions in EOLC decisions. Patients who made EOLC decisions did not receive cardiopulmonary resuscitation, mechanical ventilation, or dialysis. Conclusion: The timely intervention of the RRS in EOLC facilitates an objective assessment of the patient's medical conditions, the limitation of treatments that may be minimally beneficial to the patient, and the choice of a higher quality of care. The EOLC decision using the legal process defined in the relevant Korean Act has advantages, wherein patients can clarify their preference, the family can prioritize the patient's preference for EOLC decisions, and physicians can make transparent EOLC decisions based on medical evidence and informed patient consent.